2010
DOI: 10.1172/jci40076
|View full text |Cite|
|
Sign up to set email alerts
|

Individuals with mutations in XPNPEP3, which encodes a mitochondrial protein, develop a nephronophthisis-like nephropathy

Abstract: The autosomal recessive kidney disease nephronophthisis (NPHP) constitutes the most frequent genetic cause of terminal renal failure in the first 3 decades of life. Ten causative genes (NPHP1-NPHP9 and NPHP11), whose products localize to the primary cilia-centrosome complex, support the unifying concept that cystic kidney diseases are "ciliopathies". Using genome-wide homozygosity mapping, we report here what we believe to be a new locus (NPHP-like 1 [NPHPL1]) for an NPHP-like nephropathy. In 2 families with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 50 publications
1
96
0
Order By: Relevance
“…The highest levels were in heart followed by pancreas, kidney, testis and peripheral blood mononuclear cells (PBMCs) and other tissues. Notably, a genome-wide homozygosity mapping study of families presenting with the autosomal recessive kidney disease nephronophthisis (NPHP) detected homozygous frameshift and splice-site mutations in the gene encoding APP3 (Böttinger, 2010;O'Toole et al, 2010). This earlier study revealed that APP3, which is related to ciliary dysfunction, is a potential disease-causing protein in kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The highest levels were in heart followed by pancreas, kidney, testis and peripheral blood mononuclear cells (PBMCs) and other tissues. Notably, a genome-wide homozygosity mapping study of families presenting with the autosomal recessive kidney disease nephronophthisis (NPHP) detected homozygous frameshift and splice-site mutations in the gene encoding APP3 (Böttinger, 2010;O'Toole et al, 2010). This earlier study revealed that APP3, which is related to ciliary dysfunction, is a potential disease-causing protein in kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in XPNPEP3, a mitochondrial aminopeptidase, were identified in two independent kindred 65 with a renal phenotype characterized by tubular atrophy with interstitial fibrosis and progressive renal insufficiency. One of these kindred with an early truncating mutation presented with evidence of multiorgan system involvement and complex I deficiency in muscle biopsy.…”
Section: Posttranslational Processing Of Mitochondrial Proteinsmentioning
confidence: 99%
“…Mutations in several other nuclear-encoded genes have been reported in individuals with spectrum respiratory chain defects, including decreased activity of complex I, 65 complex III, 68 complex IV, 69 and complex V. 70 Mutations in the mitochondrial chaperone BCS1L have been associated with complex III-deficiency encephalopathy, liver failure, and proximal tubulopathy, or rarely interstitial nephritis presenting in the neonatal period.…”
Section: Respiratory Chain Assembly and Functionmentioning
confidence: 99%
“…The zebrafish system is well poised for functionally characterizing such genes and can be used to examine coding and noncoding function in vivo. Several studies using genomic approaches have identified gene variants whose function in disease pathology has been successfully tested in zebrafish, including melanoma (87), cardiomyopathy (88), polyneuropathy (89), neurodegenerative disease (90,91), and ciliopathies (92). Recently, Gieger et al carried out a high-powered meta-analysis of genome-wide association studies (GWAS) in nearly 67,000 individuals to identify putative novel regulators of megakaryopoiesis and platelet formation (93).…”
Section: Future Perspectivesmentioning
confidence: 99%